2013
DOI: 10.1080/15374416.2013.850701
|View full text |Cite
|
Sign up to set email alerts
|

Negative Peer Status and Relational Victimization in Children and Adolescents: The Role of Stress Physiology

Abstract: The purpose of the current investigation was to determine the unique associations between two subtypes of low peer status, peer rejection and unpopularity, and changes in relational victimization over time. This study also investigated if these associations were moderated by sympathetic nervous system (SNS) and parasympathetic nervous system (PNS) reactivity to peer stress. Sixty-one girls attending (M(age) = 11.91 years, SD = 1.62; predominantly Caucasian) a residential summer camp were followed across 1 cale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 58 publications
2
20
1
1
Order By: Relevance
“…Contrary to the hypotheses, relational victimization was also associated with higher levels of reactive relational aggression among individuals who displayed reciprocal parasympathetic activation (i.e., RSA augmentation and low SCL-Reactivity). This finding stands in contrast to previous research Lafko et al, 2013), which suggests that reciprocal parasympathetic activation buffers against the harmful effects of marital conflict and peer rejection in children. Reciprocal parasympathetic activation reflects a coordinated stress response from both branches of the ANS; however, PNS activation in the context of stress may lead to a failure to elicit physiological resources necessary for active behavioral engagement with the environmental demands ).…”
Section: Reactive Relational Aggressioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the hypotheses, relational victimization was also associated with higher levels of reactive relational aggression among individuals who displayed reciprocal parasympathetic activation (i.e., RSA augmentation and low SCL-Reactivity). This finding stands in contrast to previous research Lafko et al, 2013), which suggests that reciprocal parasympathetic activation buffers against the harmful effects of marital conflict and peer rejection in children. Reciprocal parasympathetic activation reflects a coordinated stress response from both branches of the ANS; however, PNS activation in the context of stress may lead to a failure to elicit physiological resources necessary for active behavioral engagement with the environmental demands ).…”
Section: Reactive Relational Aggressioncontrasting
confidence: 99%
“…Moreover, reciprocal sympathetic activation predicts better emotion regulation in children at all levels of temperamental surgency (Stifter, Dollar, & Cipriano, 2011) suggesting that reciprocal sympathetic activation reflects adaptive autonomic responding to stressors. Of particular relevance to this study, Lafko, Murry-Close, and Shoulberg (2013) found that peer rejection predicted increased peer victimization over time only among female children with coactivation or coinhibition profiles. Building upon these findings, examining unique profiles of PNS x SNS reactivity may be relevant to identifying individual differences in the link between relational victimization and relational aggression.…”
Section: Pns X Sns Interactions: a Multi-system Approachmentioning
confidence: 66%
“…For example, Vandenbroucke et al (, ) have shown that social exclusion experienced via the cyberball procedure does not produce a significant effect on children's WM performance, neither in preschool nor during school years. Interestingly, they maintained that in order to impede children's WM, social exclusion needs to be long‐lasting and, hence, associated to chronic and high levels of stress (Lafko, Murray‐Close, & Shoulberg, ). This view is also consistent with the literature on life event stress and WM impairment that shows that the greater the number of stressful events in one's life, the poorer the overall performance on WM tasks (Klein & Boals, ).…”
Section: Discussionmentioning
confidence: 99%
“…It may not always be feasible to include all levels of analysis, and genetic and physiological processes in particular are complex and may be cost prohibitive, but at a minimum an appreciation for this approach allows the scholar to consider the possible influence of the other levels and domains. A number of excellent tutorials (e.g., Murray-Close, 2013) and examples for using gene-environment interaction designs or psychophysiological methods have recently been introduced to the literature (see also two articles in this special issue: Brendgen, Girard, Vitaro, Dionne, & Boivin, 2015;Lafko, Murray-Close, & Shoulberg, 2013). An illustrative example of this approach includes a seminal publication by Banny and colleagues, which showed that peer victimization subtypes mediated the association between child maltreatment and depressive symptoms (Banny, Cicchetti, Rogosch, Oshri, & Crick, 2013).…”
Section: Crucial Future Directions and Recommendationsmentioning
confidence: 99%